Gas-filled membrane absorption: a review of three different applications to describe the mass transfer by means of a unified approach - Hasanoglu, Ayca; Romero, Julio; Plaza, Andrea; Silva, Wladimir (DESALINATION PUBL, 2013)
This work involves the presentation of a general approach to describe the gas-filled membrane absorption process by analyzing three different applications. Ammonia removal from wastewater was described in a previous work using a resistance-in-series model. In this contribution, this model has been applied to describe the HCN removal from wastewater as well as to characterize the transfer of SO2 from wines to a receiving solution to develop a new method for enhanced quantification of sulfite content. The experimental results of this novel technique for SO2 quantification and its theoretical validation are presented in this study. The analyzed operations are based on hydrophobic hollow fiber contactors, which are used to physically separate two aqueous phases: a feed solution containing a volatile compound and a reactive receiving solution. Mainly removal of three volatile compounds under this configuration was analyzed: NH3, HCN, and SO2. By this way, a unified description based on a resistance-in-series model was developed for the three chemical absorption systems, obtaining good agreement between experimental data and the predicted values. Furthermore, the extraction percentages were significantly high (up to 99.9%) for the three systems. The mass transfer model shows a significant influence of the hydrodynamic conditions of the feed solution, gas solubility, and the rate of reaction on the performance of the process.
Keywords: Membrane absorption; Mass transfer; Modeling; Ammonia; HCN; SO2; CYANIDE REMOVAL; AMMONIA REMOVAL; SULFUR-DIOXIDE; CONTACTORS; COAGULATION; DEGRADATION; TRANSPORT; VAPOR; VOCS; AIR; Engineering; Water Resources